Paul, the temple, and building a metaphor - Basham, David Anthony (London New York Oxford New Delhi Sydney T&T Clark, 2025)
"David Anthony Basham argues that Paul and the Corinthians share a "system of associated commonplaces" about the Jerusalem temple. Basham proposes that when Paul applies temple language to the Corinthians by calling them naos theou ("God's temple"), he sparks a creative process of interaction between the temple and the Corinthian assembly - a process of selecting, emphasizing, and organizing information from the source domain (temple) to see the target domain (the Corinthians) in a new light. Basham suggests that, in understanding Paul's fraught relationship with certain institutions of Second Temple Judaism and his conception of gentile inclusion, we can appreciate the creative ways in which he employs cultic imagery to describe his ministry and the ritual life of early gentile believers. By exploring the construction of metaphor, the depiction of the Jerusalem temple in Paul's letters, and Judaean religion among gentiles, Basham demonstrates that Paul's temple metaphor speaks to a new cultic reality for gentiles-in-Christ that is linked to Israel's worship, though detached from its actual expression in Jerusalem." --
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Paul -- the Apostle, Saint -- Language; Paul - the Apostle, Saint - Language; Temple of Jerusalem (Jerusalem) -- In the Bible; Temple of Jerusalem (Jerusalem, Israel) - In the New Testament; Bible -- Criticism, interpretation, etc; New Testament - Criticism, interpretation, etc; Metaphor -- Religious aspects -- Christianity; Metaphor - Religious aspects - Christianity; Hochschulschrift